Switched reluctance motor drives : fundamentals to applications - Bilgin, Berker; Jiang, James Weisheng; Emadi, Ali (CRC Press, 2018)
"This is a comprehensive textbook covering major aspects of switched reluctance motor drives in detail. It also provides a macroscopic view of the use of electric motors in different sectors to explore the role of SRM in industry. Utilizing higher efficiency, lower cost, and robust electric motors will increase the level of electrification in industry, improve overall system efficiency, and reduce the operational cost, the electricity consumption, and emissions. This is where switched reluctance machine (SRM) can play a significant role. One of the main advantages of SRM is its low-cost and simple construction, which can provide reliable operation in a harsh environment"--
Includes bibliographical references and index.
Keywords: Reluctance motors